The Evolution of the Ammonia Synthesis Catalyst 'AmoMax®-CASALE' - John D'Alessandri; Ermanno Filippi; Sergio Panza; Marvin Estenfelder; Stephan J. Reitmeier; Andreas Reitzmann; Pierdomenico Biasi; Rene Eckert (CHIMIA, 2022)
Despite the Haber-Bosch process being more than 100 years old, only incremental improvements have been achieved until recently. Now, by combining the catalyst expertise of CLARIANT and the engineering knowledge of CASALE, a breakthrough has been realized. AmoMax®-Casale is a new ammonia synthesis catalyst jointly developed by Casale and Clariant particularly for use in Casale ammonia converters. AmoMax®-Casale is a customized evolution of the well-known, wustite-based catalyst, AmoMax® 10. While retaining the same superior resistance to ageing, poisoning and mechanical strength, AmoMax®-Casale is significantly more active. This feature allows to reduce the loop recycle rate and the loop pressure and/or to increase the ammonia production. The higher activity of AmoMax®-Casale contributes to improve the overall operating efficiency either by saving energy, or by increasing significantly the plant capacity. This article will describe in detail the successful development of AmoMax®-Casale, explain advantages and commercial benefits based on concrete plant simulations and share the start-up experience of the first commercial reference.